Sistem Informasi Kelayakan TORA Berbasis Web di Kabupaten Cianjur - Dongoran, Awaluddin; Januriana, Andi Moch; Firmansyah, Devie; Wahyono, Eko Budi (LPPM UNIKA Santo Thomas Medan, 2025)
Agrarian reform is a strategic program aimed at improving land ownership distribution and enhancing community welfare. One crucial stage in this program is determining the eligibility of Tanah Objek Reforma Agraria (TORA), which requires an objective and structured selection method. This study develops a web-based system that implements the Simple Additive Weighting (SAW) method to assess TORA eligibility more efficiently and transparently. The SAW method is chosen because it provides systematic calculations by considering various established criteria, such as land legal status, land use, and social and economic potential. This system enables policymakers to manage and analyze data more effectively, thereby supporting accurate and fair decision-making in the implementation of agrarian reform. The study results indicate that a web-based approach using the SAW method can improve accuracy and efficiency in determining TORA eligibility, offering a more structured solution for agrarian reform programs in Indonesia.